ANALISIS PENGGUNAAN MEDIA TERRARIUM BERBASIS PROBLEM BASED LEARNING PADA MATERI EKOSISTEM DI SMAS NUR AZIZI TANJUNG MORAWA - Dwi Amanda; Hibatunnaila Ar-Rizki; Pretty Thalia Br Saragih; Hana Grace Samaria Sitorus; Widya Arwita; Rizal Mukra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Ecosystem learning in biology is often considered complex due to the interaction of various biotic and abiotic components, which can cause students to experience difficulties in understanding concepts when learning remains theoretical. In addition, 21st century learning demands require students to develop critical thinking and problem solving skills. Therefore, appropriate learning models and media are needed. This study aims to analyze the use of terrarium media based on Problem Based Learning (PBL) in teaching ecosystem material at SMAS Nur Azizi Tanjung Morawa. This study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving one biology teacher and 30 tenth grade students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results showed that the implementation of PBL supported by terrarium media was effective. Students were actively involved and showed positive responses. The terrarium media helped students understand ecosystem concepts more concretely and increased motivation. However, limitations in media availability and time allocation were still found. Overall, the use of terrarium media based on PBL has a positive impact on students’ learning activities and conceptual understanding.